2018
DOI: 10.1002/adhm.201800686
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Abextide, a Long‐Acting Exendin‐4 Analogue in Cynomolgus Monkeys

Abstract: Abextide, synthesized by conjugating an albumin‐binding moiety—truncated Evans blue—to glucagon‐like peptide 1 receptor (GLP‐1R) agonist exendin‐4, shows extended drug release and enhanced hypoglycemic effect in diabetic mice. The aim of this study is to evaluate the pharmacodynamics of Abextide in nonhuman primates. Two batches of elderly cynomolgus monkeys with naturally occurring diabetes are used for this study. During the whole experiment period, no abnormalities such as swelling at the injection site, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In the study, all of the elderly inpatients used hypoglycemic agents: 58.06% insulin, 35.16% used oral hypoglycemic agents, and 6.78% used both. Our study found that the use of oral hypoglycemic agents or insulin is a predictor of hypoglycemia, which is consistent with previous studies in which it was reported that hypoglycemia is commonly caused by insulin, sulfonylurea, and non-sulfonylurea insulin secretagogues [39][40] .…”
Section: Discussionsupporting
confidence: 93%
“…In the study, all of the elderly inpatients used hypoglycemic agents: 58.06% insulin, 35.16% used oral hypoglycemic agents, and 6.78% used both. Our study found that the use of oral hypoglycemic agents or insulin is a predictor of hypoglycemia, which is consistent with previous studies in which it was reported that hypoglycemia is commonly caused by insulin, sulfonylurea, and non-sulfonylurea insulin secretagogues [39][40] .…”
Section: Discussionsupporting
confidence: 93%
“…Due to the high expression profile of GLP-1R in pancreatic β-cells, GLP-1 analogs (such as exendin-4) have been modified by different methods (to prolong half-life, maintain receptor binding affinity and reduce renal drug accumulation) for theranostic purposes and serve as excellent templates for future cardiovascular drug development [178][179][180][181][182][183][184]. More importantly, these modified GLP-1 analogues have shown hypoglycemic [185,186] and cardiovascular protective effects [180,183] in different animal models. Further exploration of these modified agents in animal models of cardiometabolic diseases will deepen our understanding of the potential cardioprotective mechanisms of GLP-1 and GLP-1RAs and potentially provide future directions for precise therapeutic intervention [180].…”
Section: The Theranostic Potential Of New Modifiers Of Glp-1rasmentioning
confidence: 99%
“…The Abextide showed equivalent GLP1R binding ability to exendin-4, but an extended biological half-life (35 h; 7-fold) in Balb/c mice, and prolonged hypoglycemic effects (36 h; 3.6-fold) in db/db diabetic mice. Furthering the study of Abextide, Niu et al carried out a pharmacodynamics study in diabetic Cynomolgus monkeys [100]. The results showed that the Abextide could elicit similar levels of hypoglycemic activity with albiglutide, a clinically approved long-lasting GLP-1 agonist, and exerted hypolipidemic and anorexic activities.…”
Section: Non-covalent Albumin Bindingmentioning
confidence: 99%